The Influence of Economic Structural Changes on the Regional Labor Markets in Poland between 2005–2010 - Zieliński, Mariusz; Jonek-Kowalska, Izabela (Regional Barometer. Analyses & Prognoses, 2012)
The paper concerns changes taking place on regional labor markets in Poland in the years 2005–2010. The most important factor affecting the labor market was the accession of Poland to the European Union in this period, as it evoked the need for adjustments of a structural character. The statistical analysis presented in the paper is based on the data published by GUS (Central Statistical Office) in the Statistical Yearbooks of Regions and includes: changes of the employment sector level and structure and changes of the work productivity and wages level. The basic hypotheses were the statements that in the analyzed period there was an improvement in the employment structure according to sectors, differences in wages between the regions decreased and there was a relation between work productivity and wages. On the basis of the statistical data concerning the period 2005–2010 it was determined that, among the research hypotheses stated, only the third may be considered fully confirmed. Most of the data questions the hypothesis about the decrease of regional differences in the situation on the labor market. The changes of employment structure were only beneficial in terms of the fall in the share of employment in the second sector (heavy industry and construction) as well as the growth in employment in the third sector (services). The period of five years of 2005–2010 also brought increase, although contrary to the expected long-term tendencies, in the share of employment in the first sector.